2022
DOI: 10.1039/d2cc04379c
|View full text |Cite
|
Sign up to set email alerts
|

Cation-controlled capture of polyoxovanadate-based organic–inorganic 1D architectures

Abstract: Metal cations are used to control the selective crystallization of organic-inorganic supramolecular polymers. Two complementary monomers, a dodecanuclear vanadate [V12O32(NO3)]5- and the organic macrocycle cyclen assemble into hybrid host-guest aggregates....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…Halide template insertion into the {V 12 } structure was explored by modification of the original {V 12 } -cyclen synthesis reported earlier. 19 Briefly, the new synthesis uses reaction of ( n Bu 4 N) 4 [V 4 O 12 ] (= {V 4 } ), cyclen and a metal salt to introduce the template anion (La(NO 3 ) 3 , LaCl 3 , LaBr 3 , BaBr 2 ) in DMSO solution acidified with the corresponding (template-containing) acid ( i.e. HNO 3 /HCl aq /HBr aq ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Halide template insertion into the {V 12 } structure was explored by modification of the original {V 12 } -cyclen synthesis reported earlier. 19 Briefly, the new synthesis uses reaction of ( n Bu 4 N) 4 [V 4 O 12 ] (= {V 4 } ), cyclen and a metal salt to introduce the template anion (La(NO 3 ) 3 , LaCl 3 , LaBr 3 , BaBr 2 ) in DMSO solution acidified with the corresponding (template-containing) acid ( i.e. HNO 3 /HCl aq /HBr aq ).…”
Section: Resultsmentioning
confidence: 99%
“…Note that an earlier study had shown that the use of a La 3+ or Ba 2+ as counter-cation allows selective isolation of the {V 12 } capped with diprotonated cyclen (Table 1, compound 5 ) or triprotonated cyclen (Ba 2+ , Table 1, compound 4 ). 19…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations